2014
DOI: 10.1111/ffe.12230
|View full text |Cite
|
Sign up to set email alerts
|

Singularity analysis near the vertex of the V‐notch in Reissner's plate by coupling the asymptotic expansion technique with the interpolating matrix method

Abstract: A new numerical method for calculating the singularity orders of V‐notches in Reissner's plate is proposed in this paper. By introducing the asymptotic expansion of the generalised displacement field at the notch tip into the equilibrium equations of a plate, a set of characteristic ordinary differential equations with respect to the singularity order are established. In addition, by adopting the variable substitution technique, the obtained non‐linear characteristic equations are transformed into linear ones,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Recent reviews of such asymptotic identifications are available . Additional recent asymptotic identifications are also available …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reviews of such asymptotic identifications are available . Additional recent asymptotic identifications are also available …”
Section: Discussionmentioning
confidence: 99%
“…Often these additional identifications are for more complex local configurations than those in the references in the cited reviews: sometimes they simply fill in a gap in the literature. For classical elasticity with local configurations comprised of isotropic and piecewise homogeneous, linear elastic materials, all the stress singularities asymptotically identified that have been found to date since 2004 are discussed in the studies . Examples of stress singularities identified since 2004 for anisotropic elastic materials are given in the previous studies ; for functionally graded elastic materials; for finite strain in elastic materials; and for varying size scales …”
Section: Stress Singularity Identification: Asymptotic Analysismentioning
confidence: 94%
“…14 This theory has been applied to solve bending singularity in a notched plate. 19 Chen investigated the singular stress fields of a notched plate by using the integral transform method through FSDPT. 17 Both the moment and transverse shear force singularities were considered.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al proposed an interpolating matrix method based on FSDPT to investigate the singularities of the notched plate. 19 Chen investigated the singular stress fields of a notched plate by using the integral transform method through FSDPT. 20 In Chen's results, the stress singularity orders and the stress intensities are presented in exact forms.…”
mentioning
confidence: 99%
See 1 more Smart Citation